MEASURING THE LEVEL OF LAND DAMAGE DUE TO SAND AND GRAVEL MINING IN DUSUN SIDOREJO, TALUN VILLAGE, KEMALANG DISTRICT, KLATEN REGENCY OF CENTRAL JAVA - Irfan Dzaky Elma; Johan Danu Prasetya; Dina Asrifah (Universitas Pembangunan Nasional Veteran Yogayakarta, 2022)
Mining activities are quite a lot carried out by the people of Dusun Sidorejo, the mining is a sand and gravel mine. Sand and gravel mine in the process causes changes in shape of the landscape that have an impact on land damage. This research aims to determine the level of land damage caused by mining activity. The method used in this research is quantitative with observation, mapping, and land damage analysis which refers to Keputusan Menteri Lingkungan Hidup No. 43 Tahun 1996, with the parameters used is the height of the excavated cliffs, the slope of the excavated cliffs, the relief of the excavation base, vegetation cover, and management of top soil and overburden. Based on the measurement results of each parameter used, It was found that the level of damage that occurred at the research site was in the form of heavy damage. Effort to improve the mining site at the research area carried out by making bench terraces and revegetation using sengon tree, adjusted to the applicable regulations, KepMen LH No. 43 Tahun 1996